2014
DOI: 10.1617/s11527-014-0337-0
|View full text |Cite
|
Sign up to set email alerts
|

Improving shear strength of unreinforced masonry walls by nano-reinforced fibrous mortar coating

Abstract: The limited tensile resistance of many existing un-reinforced masonry (URM) members may represent a matter of great concern, especially when masonry constructions are located in seismic areas. For this reason, the development of innovative strengthening and repairing techniques have been the subject of several experimental studies performed in the last few years by many researchers worldwide. The present paper concerns an experimental study based on quasi static reverse cyclic tests carried out on full-scale U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 9 publications
0
23
0
Order By: Relevance
“…Unlike other similar studies [10,11]], this research not only intends to compare SRDP to other tests, but especially aims at establishing SRDP as a comprehensive and reliable test for the FRC characterization, with special focus on those structural applications in which FRC is provided in small thickness, i.e. sprayed concrete or tunnel lining applications [12], structural plaster overlays for retrofitting [13] and thin webbed elements.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike other similar studies [10,11]], this research not only intends to compare SRDP to other tests, but especially aims at establishing SRDP as a comprehensive and reliable test for the FRC characterization, with special focus on those structural applications in which FRC is provided in small thickness, i.e. sprayed concrete or tunnel lining applications [12], structural plaster overlays for retrofitting [13] and thin webbed elements.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, infill walls have so far been proportioned and verified as nonstructural elements of the building and their role in the structural response has often been underestimated or completely neglected in design practice. Several research programs have recently addressed the need for a design of masonry infill walls with appropriate detailing to enhance their seismic behaviour (Calvi and Bolognini 2001;Mohammadi and Akrami 2010;Preti et al 2012;Markulak et al 2013;Facconi et al 2014). Two different research approaches can be identified, one aiming to strengthen the infill, in order to make it a structural element able to support seismic load, the other to limit the infill frame interaction by reducing the infill strength and stiffness.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the TSFCM has demonstrated to be capable of properly reproducing the experimental bearing capacity, load deformation response and failure mode of a solid wall, used as reference (SW-R), previously tested at the University of Brescia (Facconi et al, 2015). The suitable prediction of TSFCM is herein demonstrated by comparing the overall response obtained from this approach to that experimentally measured and that determined from the numerical Disturbed Stress Field Model (DSFM).…”
Section: Numerical Modelsmentioning
confidence: 96%